2014
DOI: 10.1021/ct500528z
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Exchange for Calculation of Excitation Energies and Hyperpolarizabilities of Organic Electro-optic Chromophores

Abstract: Organic electro-optic (OEO) materials integrated into silicon-organic hybrid devices afford significant improvements in size, weight, power, and bandwidth performance of integrated electronic/photonic systems critical for current and next generation telecommunication, computer, sensor, transportation, and defense technologies. Improvement in molecular first hyperpolarizability (β), and in turn electro-optic activity, is crucial to optimizing device performance. Common hybrid density functional theory (DFT) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 59 publications
7
71
0
Order By: Relevance
“…Similarly, the 5A−5D gap is 1.27 kcal/mol with MPW1K, compared to 1.20 kcal/mol with the benchmark EOM method, although other isomers exhibit larger errors. Whether this accuracy continues in much larger systems, where the optimal fraction of HF exchange in density functionals is known to vary, 119 remains to be determined. The method, therefore, is not sufficient for numerical benchmark accuracy (and may not be sufficient to distinguish isomers which are close in energy) but the overall energy landscape for small clusters is reproduced nicely.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the 5A−5D gap is 1.27 kcal/mol with MPW1K, compared to 1.20 kcal/mol with the benchmark EOM method, although other isomers exhibit larger errors. Whether this accuracy continues in much larger systems, where the optimal fraction of HF exchange in density functionals is known to vary, 119 remains to be determined. The method, therefore, is not sufficient for numerical benchmark accuracy (and may not be sufficient to distinguish isomers which are close in energy) but the overall energy landscape for small clusters is reproduced nicely.…”
Section: Resultsmentioning
confidence: 99%
“…For all the used functionals, equilibrium geometries were computed only for the most stable conformer of each dye. Indeed at variance with dipole moments [41][42][43], ionization energies are known to exhibit a marginal dependence on conformations [22].…”
Section: Computational Detailsmentioning
confidence: 99%
“…Low-exchange hybrid GGA functionals are expected to provide reliable predictions of oxidation free energies only for donor-acceptor dyes possessing a short bridge, for which no delocalization is expected upon ionization, possibly because in that case localizing solvation effects are sufficient to balance the self-interaction error [22]. Finally high exchange and range separated GGA functionals are not a practical choice for oxidation free energies because the restricted open shell formalism has to be adopted for unpaired electron species to prevent an unphysical energy lowering due to spin contamination.…”
Section: Theoretical Vs Experimental Oxidation Potentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, our recent study of ω tuning of charge-transfer chromophores showed that the size-dependent trends in the Koopmans' optimized ω were opposite to those that gave the best agreement with experimental excitation energies. 52 The present work investigates the relationships between molecular size, delocalization error, accuracy of the computed ionization potential, and the effectiveness of ω tuning, for a series of gas-phase organic molecules. The results show that the delocalization error introduces a systematic underestimation of the IP that increases with system size and that the computed IP is also not size-extensive.…”
Section: Introductionmentioning
confidence: 99%